Turning Off the Tap: How the World Can End Plastic Pollution and Create a Circular Economy - United Nations Environment Programme (United Nations, 2023)
This report examines the economic and business models needed to address the impacts of the plastics economy. The report proposes a systems change to address the causes of plastic pollution, starting by reducing problematic and unnecessary plastic use, redesigning the system, products and their packaging and combining these with a market transformation towards circularity in plastics. This can be achieved by accelerating three key shifts – reorient and diversify, reuse, and recycle, – and actions to deal with the legacy of plastic pollution. The report highlights that solutions are available now and that a systems change, underpinned by the necessary regulatory instruments, will result in a range of economic benefits and reduce damage to human health, the environment and the climate.